2017
DOI: 10.1111/ceo.13009
|View full text |Cite
|
Sign up to set email alerts
|

Association of disease‐specific causes of visual impairment and 10‐year mortality amongst Indigenous Australians: the Central Australian Ocular Health Study

Abstract: Visual impairment was associated with all-cause mortality in a cohort of Indigenous Australians. However, diabetic retinopathy was the only ocular disease that significantly increased the risk of mortality. Visual impairment secondary to diabetic retinopathy may be an important predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We assumed a causal pathway for the association between visual impairment and mortality as depicted in Figure 1, based on previous studies [5,6,7,8,9,12,13,14,19,20,21,22], to assess the independent association by identifying potential confounders and mediators. In brief, we selected older age, systematic diseases and conditions (body mass index, waist circumference, systolic and diastolic blood pressure, serum levels of fasting glucose, creatinine, aspartate aminotransferase, alanine aminotransferase, and gamma glutamyltransferase, and history of stroke, heart disease, hypertension, type 2 diabetes, dyslipidemia, and other diseases including cancer), income, residing area, and lifestyle factors (smoking status and alcohol consumption) as potential confounders, which could affect both visual function and mortality and possibly bias the results.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed a causal pathway for the association between visual impairment and mortality as depicted in Figure 1, based on previous studies [5,6,7,8,9,12,13,14,19,20,21,22], to assess the independent association by identifying potential confounders and mediators. In brief, we selected older age, systematic diseases and conditions (body mass index, waist circumference, systolic and diastolic blood pressure, serum levels of fasting glucose, creatinine, aspartate aminotransferase, alanine aminotransferase, and gamma glutamyltransferase, and history of stroke, heart disease, hypertension, type 2 diabetes, dyslipidemia, and other diseases including cancer), income, residing area, and lifestyle factors (smoking status and alcohol consumption) as potential confounders, which could affect both visual function and mortality and possibly bias the results.…”
Section: Methodsmentioning
confidence: 99%
“…The mortality was merely 2.7% among 452 subjects without DR, while among DR patients, the mortality raised to 13.0%. Sabanayagam and coworkers [4] recruited 2,964 diabetic patients aged 40–80 years in Singapore; over a follow-up of 8.8 years, they found that the risk of all-cause mortality was significantly increased in DR patients, with a HR of 1.54 compared with subjects without DR. Few population-based studies, such as the Singapore Malay Eye Study [5] carried out in Singapore and the Central Australian Ocular Health Study [6] carried out in Austria, reported similar findings on the association between DR and mortality.…”
Section: Introductionmentioning
confidence: 85%
“…In the analysis of the subcategories, 98.4% of the deaths due to metabolic diseases (63 out of 64 deaths) were related to diabetes, and all deaths due to genitourinary diseases (all 24 deaths) were related to renal failure in the blindness group. Considering previous reports of an increased prevalence of diabetes in visually impaired individuals in Korea (adjusted OR = 2.273, 95% CI = 1.503-3.437) and reports on the relationship between mortality and diabetic retinopathy, increased mortality in the blindness group may be mainly associated with diabetes 9,16,19,21,[28][29][30][31] . In a retrospective cohort analysis of indigenous Australians, of the diverse disease-specific causes of visual impairment, only visual impairment due to diabetic retinopathy increased the 10-year mortality after adjustments for age, sex and the presence of systemic hypertension (HR = 1.70, 95% CI = 1.00-2.87, P = 0.049) 19,31 .…”
Section: Discussionmentioning
confidence: 99%
“…After the submission of the required data, the processes of reviewing and confirming the data were performed by ophthalmologists hired by the government 2,7 . The other advantage of this study was that mortality was analyzed in all age groups; many previous cohort studies enrolled only adult populations 3,15,31 . The HRs of mortality were significantly higher in both the young and the old age subgroups of the blind cohort in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation